Injection-locked frequency divider using single-injected dual-injection MOSFETs. Issue 12 (December 2015) - Jang, Sheng-Lyang; Liu, Wen-Cheng
Abstract: A wide locking range and operation range push–push divide-by-4 injection-locked frequency divider (ILFD) is proposed in the paper and was implemented in the TSMC 0.18 μm BiCMOS process. The divide-by-4 ILFD uses a cross-coupled voltage-controlled oscillator (VCO) with a parallel-tuned LC resonator for easy startup oscillation and single-ended injected dual-injection transistors. The common drain node of dual injection transistors is AC-tied to the output of a frequency doubler. At the drain-source bias of 0.8 V, and at the incident power of 0 dBm the operation range of the divide-by-4 is 3.23 GHz, from the incident frequency 15.85 to 19.08 GHz, the percentage is 18.49%. The locking range of the divide-by-4 is 1.4 GHz, from the incident frequency from 17.08 GHz to 19.08 GHz, the percentage is 11.06%. The core power consumption is 6.53 mW. The die area is 0.83×0.597 mm 2 .